Risk Management by Implementing Hazard Identification, Risk Assessment and Determinant Control (HIRADC) Method in the Research Center of the University in Surabaya, Indonesia - Ade Titis Kurniawati1, Putri Ayuni Alayyannur1, Dani Nasirul Haqi1, Tri Martiana1, Shintia Yunita Ar (Institute of Medico-legal Publications Pvt Ltd, 2020)
The Research Center of the Faculty of Dentistry, Universitas Airlangga is one of workplaces that have various risks to cause occupational accidents. The use of various chemicals, specimens, and special instruments at the Research Center has potential to cause various risks that can threaten workers, assets, and environment. To prevent and control every hazard with potential negative risks, a risk management using HIRADC method must be implemented. This study aims to implement Hazard Identification, Risk Assessment and Determinant Control (HIRADC) method in the Research Center of the Faculty of Dentistry, Universitas Airlangga. This study is descriptive research with a cross-sectional design. Data collection was done through direct observation in the workplace and interview with a laboratory worker at the Research Center. The Research Center of the Faculty of Dentistry, Universitas Airlangga has a moderate risk. The research results showed that of the 5 work activities, there were 20 potential hazards with 20 risks identified. Based on the risk assessment, there are 1 extreme risk, 1 high risk, 11 moderate risks, and 7 low risks. The extreme risks identified are explosion, fire, and death caused by LPG. The high risks identified are explosion, poisoning, and death caused by CO2 gas. Based on the determinant control, there are 15 controls implemented including substitution control, engineering control, administration control, and wearing personal protective equipment. However, there are still 5 controls that have not been implemented. Further recommendations are needed for 5 controls that have not been implemented in every activity conducted in the Research Center of the Faculty of Dentistry, Universitas Airlangga.